First report of leaf spot on oil palm caused by Phyllosticta capitalensis in Malaysia - Nasehi, A.; Sathyapriya, H.; Wong, M. Y. (American Phytopathological Society, 2020)
Oil palm (Elaeis guineensis Jacq.) is the most economically important crop in Malaysia and the world’s highest yielding oil crop. In March 2018, irregular spots with gray centers, dark brown edges, and chlorotic halos were observed on the leaves of oil palm trees of Tenera genotype planted at Block A, University Agriculture Park, Universiti Putra Malaysia, Malaysia. The area of production is 8 ha of conventional farming with temperature and humidity ranging from 33 to 34°C and 30 to 70%, respectively. There were a total of 1,192 oil palm trees in the area analyzed, and the disease incidence was estimated to be approximately 20%. Twelve leaf sections (5 mm2) of four diseased leaves from four different symptomatic oil palm trees were surface sterilized in 1% sodium hypochlorite for 2 min, rinsed twice with distilled water, dried on sterilized tissue paper, plated on potato dextrose agar (PDA) plates, and incubated at 27 ± 1°C for 14 days in the dark. A total of 12 single-spore isolates were obtained from all sampled leaf tissues. The single colonies of all fungal isolates were olivaceous greenish to olivaceous black with an irregular light olive margin on PDA. Conidia were obpyriform or nearly elliptic, unicellular, with a hyaline, unstable apical appendage, 5 to 12 µm long. The size of conidia was 10 to 15 μm in length and 6 to 8 μm in width. These morphological characters were consistent with the original description of Phyllosticta capitalensis (Glienke et al. 2011; Hennings 1908). For fungal identification to species level, the internal transcribed spacer region (ITS) of the representative isolate UPM-Ph1 was amplified utilizing the universal primers ITS5/ITS4 (White et al. 1990) and then sequenced. The 620-bp ITS sequence was deposited in GenBank under accession number MH699964. The phylogenetic analysis confirmed that the isolate UPM-Ph1 belonged to P. capitalensis, and it shares 100% homology with the ITS sequence of the reference pathogenic P. capitalensis strain CPC18884 (GenBank JF261465), which was isolated from the host Stanhopea graveolens in Brazil, as reported by Glienke et al. (2011). Pathogenicity testing was conducted by artificial inoculation of healthy oil palm (Tenera GH 500 series) leaves with isolate UPM-Ph1 under the conditions of 9-h day/15-h night cycle and using LED white light. Four leaves were wound inoculated in three parts with a sterile scalpel and pipetting a 10-µl droplet of a conidial suspension (106 conidia/ml) on each wound. Another four leaves were wound inoculated with sterilized distilled water and served as a control. All inoculated leaves and control leaves were incubated in a chamber with 98% relative humidity at 27 ± 1°C. After 7 days, typical lesions identical to those observed in the field appeared on the inoculated leaves but not on control leaves. P. capitalensis was successfully reisolated only from the inoculated leaves and identified by morphological observations. The pathogenicity test was repeated, and the same typical lesions were observed. P. capitalensis has been reported as a weak plant pathogen that causes various diseases in plants (Wikee et al. 2013a, 2013b). Unsuccessful reisolation of the fungus from the control leaves confirmed that the control plants were not already latently infected with the pathogen. To our knowledge, this is the first report of P. capitalensis causing leaf spot disease of oil palm in Malaysia. This pathogen is capable of affecting the health and yield of oil palm trees in the plantations substantially if no control measure is in place. Therefore, further investigation is needed to determine the distribution of P. capitalensis in oil palm plantations in Malaysia.